Wound healing properties of selected tropical fruits in Malaysia: a narrative review - Mohamed, Emida; Hassan Cheong, Nur Dayana; Amran, Ain Najihah; Haron, Norhisham; Camalxaman, Siti Nazrina; Rambely, Azlin Sham (Faculty of Health Sciences, Universiti Teknologi MARA, 2025)
Reduction in healing time is crucial for minimizing pain and preventing wound-related complications. Wound dressings and topical products such as antibiotics are commonly used in chronic wound management; however, they can be costly and may be associated with adverse effects. Consequently, natural products have emerged as promising alternatives, as numerous plants and fruits possess wound-healing properties. This review focuses on five fruits from different genera—banana, papaya, mangosteen, pomegranate, and pineapple—that have been scientifically validated for their wound-healing potential between 2010 and 2025. Relevant studies were identified using the Scopus, PubMed, and ScienceDirect databases. Most wound-healing investigations employed in vivo models, demonstrating the efficacy of fruit extracts in accelerating wound closure and tissue repair. Although these fruits have shown significant wound-healing activity in experimental settings, further research, including the isolation and characterization of bioactive compounds, is necessary before the development of safe and widely accepted herbal therapies for wound management.